Sol-Gel Combustion-Assisted Electrostatic Spray Deposition for Durable Solid Oxide Fuel Cell Cathodes - Lee, Jongseo; Bang, Sehee; Lee, Wonyoung (Frontiers in Chemistry, 2022)
The chemical instability of perovskite oxides containing Sr is a critical issue for the long-term operation of solid oxide fuel cells. In this study, we demonstrate a remarkable improvement in the chemical and electrochemical stability of a heterostructured La0.6Sr0.4CoO3-δ (LSC)-Ce0.9Gd0.1O1.95 (GDC) electrode. Electrostatic spray deposition was employed to fabricate heterostructured nanoparticles in a single step with a coaxial nozzle supplying the LSC powders in the core nozzle and the GDC precursors in the shell nozzle. Moreover, the reducing fuel added to the GDC precursor solution induced the sol-gel combustion reaction in the droplet to form a uniform nanocrystalline GDC coating with high surface coverage. The high surface coverage of GDC on the LSC more significantly improved long-term stability compared with than of the bare LSC cathode at a constant current density of 1 A/cm2 at 600 °C for 100 h.